Characteristics and intrasubject variation in the respiratory microbiome in interstitial lung disease. Issue 14 (7th April 2023) - Cho, Jun Yeun; Kim, Mi Yeon; Kim, Ji Hyoun; Kim, Eung-Gook; Kim, Sun-Hyung; Yang, Bumhee; Kang, Hyeran; Lee, Ki Man; Choe, Kang Hyeon; Shin, Yoon Mi
Abstract : Recent studies have reported that the lower airway microbiome may play an essential role in the development and progression of interstitial lung disease (ILD). The aim of the current study was to evaluate the characteristics of the respiratory microbiome and intrasubject variation in patients with ILD. Patients with ILD were recruited prospectively for 12 months. The sample size was small (n = 11) owing to delayed recruitment during the COVID-19 pandemic. All subjects were hospitalized and were evaluated by a questionnaire survey, blood sampling, pulmonary function test, and bronchoscopy. Bronchoalveolar lavage fluid (BALF) was obtained at 2 sites, the most and least disease-affected lesions. Sputum collection was also performed. Furthermore, 16S ribosomal RNA gene sequencing was performed using the Illumina platform and indexes of α- and β-diversity were evaluated. Species diversity and richness tended to be lower in the most-affected lesion than in the least-affected lesion. However, taxonomic abundance patterns were similar in these 2 groups. The phylum Fusobacteria was more prevalent in fibrotic ILD than in nonfibrotic ILD. Inter-sample differences in relative abundances were more prominent in BALF versus sputum specimens. Rothia and Veillonella were more prevalent in the sputum than in BALF. We did not detect site-specific dysbiosis in the ILD lung. BALF was an effective respiratory specimen type for evaluating the lung microbiome in patients with ILD. Further studies are needed to evaluate the causal links between the lung microbiome and the pathogenesis of ILD.